Effect of Myopic Femtosecond Laser-Assisted LASIK on Anterior Chamber Inflammation (Flare Values) and Corneal Endothelium: A Prospective before and after Study - Kemal Turgay Özbilen; Emre Altinkurt; Nihan Aksu Ceylan; Gizem Sayar Bilgin; Nilüfer Gözüm (Journal of Ophthalmology)
Purpose. This study aimed to investigate whether femtosecond laser-assisted LASIK (FS-LASIK) surgery causes inflammation in the anterior chamber and to analyze its effect on endothelial cells. Methods. This prospective, longitudinal study included left eyes of 30 patients (19 females) who had undergone FS-LASIK surgery due to myopia and myopic astigmatism. Endothelial cell density (ECD) and morphological measurements were performed using a specular microscopy, and laser flare photometry was used to measure the anterior chamber flare values on the day of surgery. iFS™ Advanced FS and VISX STAR S4-IR Wavescan Excimer Laser platforms were used. Flare measurements were repeated on the postoperative 1st day and 7th day and the 1st and 3rd months. The endothelial measurements were repeated in the 3rd month. Results. Preoperatively, the mean flare was 5.59 ± 1.24 photons/ms; it was 6.49 ± 2.42 on the postoperative 1st day, 5.87 ± 2.27 on the 7th day, 5.68 ± 1.66 on the 1st month, and 5.35 ± 1.24 on the 3rd month. A significant difference was observed only between the preoperative and postoperative 1st day flare values (p=0.047). The decrease in the ECD was clinically insignificant but statistically significant, with an average of 97.0 ± 209.9 cell count/mm2 (3.3%, p=0.017). However, there was no significant change in the coefficient of variation (p=0.448) and hexagonality (p=0.096). No significant correlation was found between the increase in the flare value on the postoperative 1st day and variables. A significant correlation was found between the decrease in ECD and the preoperative ECD (r = 0.356, p=0.027). Conclusion. FS-LASIK caused minimal inflammation in the anterior chamber on only the 1st postoperative day; additionally, a minimal decrease of cell count with no morphological changes were noted in the endothelial cells on postoperative 3rd month. This trial is registered with NCT04899258.